Behavioral Learning Theory Applied In PAI Learning At Sdit Juara - Ani, Destri; Sari, Dewi Purnama; Sari, Rini Puspita (Al-Riwayah : Jurnal Kependidikan, 2023)
Behavioristic theory, which places a strong emphasis on improving personal conduct, is ideally suited for use in educational settings, particularly in the study of Islam. It is evident that subject teachers have used behavioristic theory extensively to promote positive student behavior since its inception. regardless of the learning of Islamic Education (PAI) itself, discussing associated behavior. Since PAI learning is a subject that all schools must provide. Students' behavioural modifications can be realized by giving them stimuli that will elicit positive responses. This study aims to comprehend the significance of using behavioristic theories in the study of Islamic Religious Education.The author's method is descriptive qualitative, and it includes methods for gathering data such interviews, observation, and documentation.Based on the findings of the author's research, it was determined that SDIT Juara did a good job of applying behaviorist learning theory to PAI learning. Positive behavioral changes in the students, such as increased drive for learning, interaction, memory improvement, and tolerance, are what define it. It is well known that SDIT Juara uses the behavioristic learning theory in its teaching of Islamic religious education. This theory is thought to be the best source of information to use when learning Islamic Religious Education, and it is hoped that by using this theory, it will be possible to see improvements in student conduct.